PENYALAHGUNAAN NARKOTIKA DI KALANGAN APARATUR SIPIL NEGARA YANG ADA DI KABUPATEN MAMASA - Firdiansyah, Hardi (Indonesian Journal Of Law Studies, 2022)
This study aims to determine the application of sanctions against the State Civil Apparatus as narcotics abusers in Mamasa District, and to find out whether rehabilitation sanctions for victims of narcotics abuse can cause a deterrent effect. This research is a type of legal research with empirical aspects or a type of non-doctrinal legal research or a type of socio-legal research with a qualitative descriptive research approach. This study uses secondary data as initial data to be followed up with primary data or field data. This means that empirical juridical research still relies on normative premises where operational definitions can be taken from laws and regulations to then look at the reality on the ground. The results of the study showed that the Polewali Mandar District Court had imposed sanctions on one of the State Civil Apparatuses serving in the Regional Government of Mamasa Regency who had abused the Narcotics of the Shabu Type with a sentence of 8 (eight) months of rehabilitation, but from the decision of the Polewali Mandar District Court the Prosecutor The public was dissatisfied with the court's decision so that the Public Prosecutor made an appeal to the High Court, from the results of the appeal at the High Court the defendant received a sanction of 1 (one) year in prison and 8 (eight) months of rehabilitation, after receiving a sanction from the High Court the defendant did not accept the results of the decision, then the defendant also appealed to the Supreme Court and is still waiting for a decision from the Supreme Court.